2022
DOI: 10.3390/land11111989
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics and Influencing Factors of Rural Settlements in Metropolitan Fringe Area: A Case Study of Nanjing, China

Abstract: Rural settlement is the core content of rural geography research. Exploring the spatial distribution characteristics and influencing factors of rural settlements can provide reference for the optimization of rural settlements. This paper selected Nanjing as a typical case, based on remote sensing image, using R statistics, kernel density analysis, hot spot detection analysis and semi variogram function; the paper analyzed the spatial, scale and morphological distribution characteristics of rural settlements; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…This settlement pattern is clustered to form small and diffuse units [10]. The centralized pattern is a pattern of residential settlements in which the houses are built at one point.…”
Section: Centralized Settlement Patternsmentioning
confidence: 99%
“…This settlement pattern is clustered to form small and diffuse units [10]. The centralized pattern is a pattern of residential settlements in which the houses are built at one point.…”
Section: Centralized Settlement Patternsmentioning
confidence: 99%
“…B. Zhang, 2020); villages in poor areas in southwest China (L. Yao, Li, Chen, Wang, & Peng, 2020); oasis villages in Xinjiang (Lin, Lei, Wu, Yang, & Li, 2020); and various other types of rural settlements in terms of size, density, and shape. Scholars have analysed the evolution of size, density and shape, and the relationship between their evolution and indicators such as slope elevation, agricultural technology, non-agricultural population, industrial output value, and net income per capita.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the research regarding the evolution of rural settlements' spatial pattern and its influencing factors, a large number of scholars have used spatial analysis methods, geographically weighted regression models, and geographic detectors to investigate rural settlements in suburban counties (C. C. Liu, 2020); traditional settlements in Youshui Basin (Du & Guo, 2020); rural settlements in Hexi, Gansu (R. Y. Li, 2020); rural settlements in wetland landscapes (K. Y. Li & Peng, 2020); rural settlements on urban islands (Cui & Yan, 2020); rural settlements in the poverty belt of Beijing, Tianjin, and Hebei (Tao, Zhang, Xu, Zhang, & Zhang, 2020); rural valley settlements (Xu & Zhao, 2020); rural settlements in near urban areas (Chen, 2020), Dingziwan area in Jiaodong (J. B. Zhang, 2020); villages in poor areas in southwest China (L. Yao, Li, Chen, Wang, & Peng, 2020); oasis villages in Xinjiang (Lin, Lei, Wu, Yang, & Li, 2020); and various other types of rural settlements in terms of size, density, and shape. Scholars have analysed the evolution of size, density and shape, and the relationship between their evolution and indicators such as slope elevation, agricultural technology, non‐agricultural population, industrial output value, and net income per capita.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, many scholars have found that the distribution and evolution of rural settlements are largely influenced by a range of factors, including the natural environment and socio-economic conditions [14,15,17,39], and there is a significant regional disparity in the dominant factors [40,41]. With the continuous advancement of socio-economic conditions and technological progress, the constraining effect of natural conditions, for example, slope and water sources, on rural settlements has gradually diminished [17], while the influence of socio-economic factors has become more dynamic and diversified [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…As the dynamic evolution of rural settlements has been widely known as a result of a combination of factors in the complex socio-economic transformation [7], this paper, therefore, will attempt a larger scale analysis. Though knowledge about the spatial patterns of rural settlements has been explored in provinces [45,46], metropolitan areas [39], and various urban agglomeration areas [47][48][49], systematic research on the changes of rural settlements in the three provinces located in the MRYRR remain scarce, and research on the influencing factors, especially from the aspect of socio-economic factors, are even more inadequate. The MRYRR is located in Central China with diverse landform types.…”
Section: Introductionmentioning
confidence: 99%